(untitled) (Doctor Virtualis, 2023)
Starting from some aspects of the contemporary debate on metaphor, the article proposes a path through various figures of artifex to question the philosophical, cognitive and heuristic aim of analogy and defend its rhetorical dimension. The theme of the artifex and his creative-productive process often appears in the form of analogy. It has undergone significant variations throughout history, most notably the displacement of the domain and purpose of analogy from the transcendent to the immanent. An itinerary is proposed that begins with the Franciscan Bonaventure of Bagnoregio, who shares the main features of the Augustinian and monastic metaphysics of relationship in which the analogy of proportionality plays a central role not only in the structure of being, but also in the progress of knowledge. The question in the modern age is addressed with brief references to some figures of the Renaissance (Leon Battista Alberti, Leonardo da Vinci) and modern age (Baudelaire, Kandinsky) in which the interest shifts to immanence. Finally, the role of analogy in the creative processes outlined by Paul Valéry is explored, where it becomes the main function of the universal power of the mind. Concluding remarks are proposed, firstly theoretical, on the philosophical, cognitive and heuristic dimension of analogy in different historical periods; and then methodical on the use of analogy in the history of philosophy.